Hunger Eradication and Poverty Reduction in Vietnam: Achievements and Lessons Learned - TUAN, DR. NGUYEN MINH (The journal of contemporary issues in business and government, 2021)
Over the past three decades, poverty reduction has always been an area that has achieved many impressive successes in the economic development process of Vietnam. Along with high economic development, a series of policies on hunger eradication and poverty reduction has been implemented synchronously at all levels, provinces and cities nationwide with funding mobilized from the Government, communities and International social organizations have significantly improved the face of poverty in all regions of the country. Vietnam has become one of the leading countries in the Asia-Pacific region in applying multidimensional poverty measures to reduce poverty in all dimensions. The study focuses on analyzing the current situation of poverty reduction in Vietnam, thereby pointing out lessons learned to continue Vietnam’s poverty reduction strategy in the coming time.